Simulation of a Crash Test of a Single-Track Vehicle in a Frontal Collision, Part1 - Rafal FENC; Marek STEMBALSKI (Communications of International Proceedings, 2021)
This paper describes the first part of the results of a frontal crash test simulation of a single-track vehicle with a wall. The scope of the work included the development of a geometric and computational model of an electric scooter single-track vehicle frame, along with additional components necessary to perform crash simulations for given boundary conditions, using CAD systems. The geometric model was made using SolidWorks software while the computational model was made using Abaqus CAE software. Strength calculations were performed based on the finite element method. The computational model was performed using shell elements. The simulation resulted in a frontal crash test at 45 km/h.
Keywords: Crash Test; Single-Track Vehicle; Numerical Simulation; Mechanical Engineering.